STIMULASI PIJAT BAYI UNTUK TUMBUH KEMBANG BAYI YANG OPTIMAL PI POSYANDU BTN CIERENG RT 045 KABUPATEN SUBANG - Ika Rahman; Diva Hanuun Haniifah; Hagina Kurnia Putri; Christiana Veronica Yustin (Insight Power (Kekuatan Wawasan), 2022)
Baby massage is also known as stimulus touch or touch therapy. It is called touch therapy because it is through this baby massage that there will be comfortable and safe communication between the mother and her baby. This social service is giving baby massage for optimal growth and development. This activity was carried out at the Posyandu BTN Ciereng which is located in Kab. Subang. The purpose of this activity is to increase the baby's sense of comfort, and provide fitness. The results of this activity showed an increase in comfort, fitness, good fine and gross motor skills, and a good baby mood. This shows that baby massage optimizes growth and development, including improving the baby's fitness and providing stimulation to babies is important for baby's growth and development.Keywords: Baby, Baby Massage, Stimulation, Development